Editor's Choice-Effects of targeted temperature management on mortality and neurological outcome: A systematic review and meta-analysis. Issue 5 (1st August 2018) - Stanger, Dylan; Mihajlovic, Vesna; Singer, Joel; Desai, Sameer; El-Sayegh, Rami; Wong, Graham C
Abstract: Aims: The purpose of this study was to conduct a systematic review, and where applicable meta-analyses, examining the evidence underpinning the use of targeted temperature management following resuscitation from cardiac arrest. Methods and results: Multiple databases were searched for publications between January 2000–February 2016. Nine Population, Intervention, Comparison, Outcome questions were developed and meta-analyses were performed when appropriate. Reviewers extracted study data and performed quality assessments using Grading of Recommendations, Assessment, Development and Evaluation methodology, the Cochrane Risk Bias Tool, and the National Institute of Health Study Quality Assessment Tool. The primary outcomes for each Population, Intervention, Comparison, Outcome question were mortality and poor neurological outcome. Overall, low quality evidence demonstrated that targeted temperature management at 32–36°C, compared to no targeted temperature management, decreased mortality (risk ratio 0.76, 95% confidence interval 0.61–0.92) and poor neurological outcome (risk ratio 0.73, 95% confidence interval 0.60–0.88) amongst adult survivors of out-of-hospital cardiac arrest with an initial shockable rhythm. Targeted temperature management use did not benefit survivors of in-hospital cardiac arrest nor out-of-hospital cardiac arrest survivors with a non-shockable rhythm. Moderate quality evidence demonstrated no benefit of pre-hospital targeted temperature management initiation. Low quality evidence showed no difference between endovascular versus surface cooling targeted temperature management systems, nor any benefit of adding feedback control to targeted temperature management systems. Low quality evidence suggested that targeted temperature management be maintained for 18–24 h. Conclusions: Low quality evidence supports the in-hospital initiation and maintenance of targeted temperature management at 32–36°C amongst adult survivors of out-of-hospital cardiac arrest with an initial shockable rhythm for 18–24 h. The effects of targeted temperature management on other populations, the optimal rate and method of cooling and rewarming, and effects of fever require further study.